ASSESSING LOCAL PORE WATER VELOCITY ALONG PREFERENTIAL FLOW IN EARTHEN DAM USING SALT TRACER - Huynh Thi Thu , Huong; Le Van, Son; Tran Trong, Hieu; Phan Thi, Luan; Vuong Duc, Phung; Lai Viet, Hai (Malaysian Journal of Science, 2024)
The local pore water velocity along the preferential flow path signifies the hydraulic parameter responsible for erosion within an earthen dam. This study introduces an empirical approach to ascertain the local pore water velocity within the earth dam’s leakage zones by monitoring the travel time of the salt tracer through the corresponding electric potential anomalies in the ground. The alignment of electric potential anomalies with the movement of the salt tracer plume over time was confirmed through experiments on a physical model coupled with numerical simulations. The pore water velocity, calculated based on the location of the maximum electric potential anomaly, demonstrated excellent agreement with the experimental value, with an error of under 6%. For illustrative purposes, a field-scale salt tracer test was conducted at a leaking earthen dam in Vietnam. The tracer breakthrough curve originating from the leakage point revealed that the seepage water’s travel time is approximately 40 days. The results of electric potential anomalies over time indicate that the pathway of seepage flow from upstream to the leakage point forms a horizontal V-shape, with the local pore water velocity ranging from 1.7 to 9.9x10-5 m/s. These local pore water velocities are subsequently compared with the critical seepage velocity to assess in-situ information regarding the internal erosion status of the target dam.